Narrative Review on Dietary Modulation of Inflammation in Nephrotic Syndrome and Chronic Kidney Disease - Elramli, Safia S.; Ibrahim, Naser H. (International Journal of Health Sciences, 2026)
Purpose: The purpose of this study is to investigate the role of chronic inflammation in the progression of nephrotic syndrome (NS) and chronic kidney disease (CKD), with a focus on mechanisms including glomerular injury, proteinuria-induced tubular NF-κB activation, oxidative stress, uremic toxin accumulation, gut dysbiosis, and their contribution to cardiovascular complications and progression to end-stage renal disease (ESRD). Methodology: Literature searches from inception to December 20, 2025, were performed on PubMed, google scholar, and the Since Direct using key words such as chronic kidney disease, inflammatory markers, nephrotic syndrome were related terms. All relevant studies in the review focusing on proinflammatory, inflammatory biomarkers included if sufficient data were available. Findings: Anti-inflammatory dietary strategies in CKD and NS patients show potential to lower proinflammatory marker levels. Larger, multicenter randomized controlled trials (RCTs) are needed to establish efficacy, safety, and quality-of-life benefits. Unique Contribution to Theory, Policy and Practice: This review uniquely contributes by integrating dietary modulation into the inflammation-driven pathophysiology of CKD and NS, offering a mechanistic, clinically relevant, and policy-informing framework for nutrition-based interventions.